The Development of eLEMA-SCL Protozoa for Invertebrate Zoology Courses - Haryono, Agus; Basuki, Bejo; Adam, Chaidir; Savitri, Shanty; Araina, Elga; Fahrina, Ririn (International Conference on Elementary Education, 2021)
The development of electronic learning materials is very necessary for the midst of the COVID-19 pandemic which requires lecture activities to be carried out online. This was carried out to support physical distancing to break the chain of transmission of COVID-19. Currently, there are not many electronic learning materials available that lead to student-centered learning (SCL) and can be implemented amid the COVID- 19 pandemics. The purpose of this research is to develop an eLEMA (Electronic Learning Material) application, an Android-based electronic learning material with content or material that can be accessed online and offline, and with features that make it easier for users to operate. This research is a research development (Research and Development; R & D) to develop Android-based ELEMA-SCL Protozoa (Electronic Learning Material-Student Centered Learning) for Zoology courses. This development model consists of 3 phases of approach, namely: (1) Phase 1: Needs Assessment; (2) Phase 2: Design; and (3) Phase 3: Develop / Implement. The product developed in the form of an Android-based eLEMA application made using the MIT App Inventor is feasible to implement. The implementation results show: (1) the effectiveness of online and offline lectures with a gain value of 0.52 in the Medium category; (2) student response to the implementation of eLEMA is positive. Thus, the eLEMA application can be used for online and offline lectures during the COVID-19 pandemic.